Cargo Cult Strange Stories of Desire from Melanesia and Beyond - Lindstrom, Lamont (University of Hawai'i Press, 2018)
Who is not captivated by tales of Islanders earnestly scanning their watery horizons for great fleets of cargo ships bringing rice, radios and refrigerators - ships that will never arrive? Of all the stories spun about the island peoples of Melanesia, tales of cargo cult are among the most fascinating.The term cargo cult, Lamont Lindstrom contends, is one of anthropology's most successful conceptual offspring. Like culture, worldview and ethnicity, its usage has steadily proliferated, migrating into popular culture where today it is used to describe an astonishing roll-call of people. It's history makes for lively and compelling reading. The cargo cult story, Lindstrom shows, is more significant than it at first appears, for it recapitulates in summary form three generations of anthropological theory and Pacific studies.Although anthropologists' enthusiasm for the notion of cargo cult has waned, it now colors outsiders' understanding of Melanesian culture, and even Melanesians' perceptions of themselves. The repercussions for contemporary Islanders are significant: leaders of more than one political movement have felt the need to deny that they are any kind of cargo cultist.Of particular interest to this history is Lindstom's argument that accounts of cargo cult are at heart tragedies of thwarted desire, melancholy anticipation and crazy unrequited love. He makes a convincing case that these stories expose powerful Western scenarios of desire itself-giving cargo cult its combined titillation of the fascinating exotic and the comfortably familiar.